2007
DOI: 10.1159/000107393
|View full text |Cite
|
Sign up to set email alerts
|

Neuroplasticity and Cellular Therapy in Cerebral Infarction

Abstract: Stroke is the second to third most common cause of death in adults, and more than a third of people who survive a stroke will have severe disability. Therapeutic options currently centre on fibrinolytic treatment, but its limitations restrict use to a small proportion of patients. Although a wide range of neuroprotective substances has been effective in experimental models, they have repeatedly failed in clinical trials because of toxicity or loss of effectiveness. Recent strategies based on neuroplasticity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 279 publications
0
4
0
1
Order By: Relevance
“…We explored infusion with stem cells and physiotherapy as a combination therapy to look into behavioral recovery after stroke. Our aim to administer stem cells intravenously was based on the hypothesis that intravenously administered stem cells will help to upregulate growth factors within the body and brain making the host environment conducive for behavioral recovery [18, 19], as it is known that enriched environment, physical activity, stress or molecules such as BDNF, VEGF and dextroamphetamines lead to reorganization of brain areas [46, 47, 48]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We explored infusion with stem cells and physiotherapy as a combination therapy to look into behavioral recovery after stroke. Our aim to administer stem cells intravenously was based on the hypothesis that intravenously administered stem cells will help to upregulate growth factors within the body and brain making the host environment conducive for behavioral recovery [18, 19], as it is known that enriched environment, physical activity, stress or molecules such as BDNF, VEGF and dextroamphetamines lead to reorganization of brain areas [46, 47, 48]. …”
Section: Discussionmentioning
confidence: 99%
“…production of growth and trophic factors, stimulation of endogenous neurogenesis and modulation of neuroinflammation. They are known to influence the environment by reorganizing the brain, and promoting learning in the form of synaptogenesis and dendritic sprouting [19, 20]. Transplanted stem cells also interact with the host tissue by forming connections and by providing ‘scaffolds’ to an injured brain in order to rescue dysfunctional and dormant cells [21].…”
Section: Introductionmentioning
confidence: 99%
“…Stroke typically demonstrates the ability of the adult mammalian brain to reorganize its circuitry following an insult [55]. The possibility that grafted cells can take part in remodeling events has been shown mainly for locally implanted neural SC [38,45,46,47], although Liu et al [56] have reported the ability of BMSC injected intravenously to promote axonal sprouting in the host parenchyma. Studies are still expected to fully characterize the long-term benefits of these approaches.…”
Section: The Acute Versus the Chronic Phasementioning
confidence: 99%
“…L'observation clinique suggère que dans les jours et semaines qui suivent la survenue d'un accident vasculaire cérébral, une récupération fonctionnelle est encore possible, par exemple sous l'effet de la kinésithéra-pie. Cette capacité de récupération est probablement liée à la plasticité cérébrale, favorisée par la mise en jeu spontanée de mécanismes endogènes, dont celle des facteurs neurotrophiques comme le BDNF (brain-derived neurotrophic factor) qui améliore la récupération fonctionnelle [33]. Compte tenu des difficultés d'utilisation thérapeutique des facteurs neurotrophiques (passage de la barrière hémato-encéphalique, risques inhérents à une administration prolongée de facteurs de croissance), les recherches se sont portées sur l'évaluation de médi-TIRÉS À PART R. Bordet caments agissant directement ou indirectement sur ces facteurs neurotrophiques, comme les antidépresseurs inhibiteurs de la recapture de la sérotonine ou le méthylphénidate dont l'effet sur la récupération fonctionnelle au décours des accidents vasculaires cérébraux ischémiques est en cours d'évaluation [34].…”
Section: Intérêt Des Molécules Exerçant Une Action Pléiotropeunclassified